Analisis Perbandingan Kinerja Algoritma Load Balancer NGINX pada Studi Kasus PRS - William Chen; Agustinus Noertjahyana; Justinus Andjarwirawan (Jurnal Infra, 2019)
The development of technology will certainly create new problems, where more client activity will be available to access existing servers. One example is the activity of registering an online study plan at Petra Christian University. Where most students log in simultaneously into the PRS system which results in full access to the server.This study will conduct a trial with the implementation of a container using a docker. Containerization technology is a very effective way to run an application. Where with containerization, it will set the entrance from the client to the server via the docker assistance and with some of the algorithms it has, namely Round Robin, hashes and Least Connection.With the tests carried out it can find the algorithm of the NGINX load balancer which is the most effective and efficient when distributing workload to the web service available in the online PRS case study. So that the PRS process going forward using existing algorithms becomes more effective and efficient.